CLINICAL ASPECTS OF SLEEP DISORDERS IN PATIENTS WITH PARKINSON’S DISEASE - O A Andrienko (Клиническая практика, 2017)
According to the scientific literature of sleep disturbance in patients with Parkinson’s disease meet from 51 to 85 %. In this study, PD patients with sleep disturbances were found in 50.1% (348 of 694 patients) were included in the registry (it surveyed patients with PD, aged from 21 to 90 years with different stages of BP living in different cities and districts of the Rostov region), noted sleep disorders during the disease, as well as to verify the diagnosis of PD. In the future, EEG-somnography were selected 48 patients with BP stage 2 on the Hoehn-Yahr, aged 52 to 71 years, and 50 healthy volunteers aged 49 to 67 years. It is established that in patients with PD stage of sleep you go faster - less time awake, and time of stage 1 non-REM sleep and the stage of paradoxical sleep (PS) in comparison with healthy volunteers. Chronic dyssomnia may occur due to ingestion of antiparkinson medications. Sleep duration decreases, but the psychological need remains the same. Structural changes are observed in sleep are significantly reduced slow-wave stage of sleep, some to a lesser extent, REM-phase and total sleep time.